2015
DOI: 10.2147/ndt.s93520
|View full text |Cite
|
Sign up to set email alerts
|

Psychological changes in alcohol-dependent patients during a residential rehabilitation program

Abstract: BackgroundAlcohol-dependent patients usually experience negative affects under the influence of alcohol, and these affective symptoms have been shown to decrease as a result of alcohol-withdrawal treatment. A recent cognitive–affective model suggests an interaction between drug motivation and affective symptoms. The aim of this multicenter study was to evaluate the psychological changes in subjects undergoing a residential rehabilitation program specifically designed for alcohol addiction, and to identify at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Indeed, polysubstance abusers run the risk of developing an addiction to multiple substances and have an increased risk of developing serious physical and mental diseases. This is in line with a previous study among patients in a residential rehabilitation program, which showed that the polyabuser group scored higher in depression, anxiety, and psychological distress compared to the pure alcoholics group 6. Furthermore, a recent meta-analytic review of psychosocial interventions for substance use disorders found that treatments targeting polysubstance use were less effective and had the lowest percentage of posttreatment abstinence compared to other interventions for substance dependence 44.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, polysubstance abusers run the risk of developing an addiction to multiple substances and have an increased risk of developing serious physical and mental diseases. This is in line with a previous study among patients in a residential rehabilitation program, which showed that the polyabuser group scored higher in depression, anxiety, and psychological distress compared to the pure alcoholics group 6. Furthermore, a recent meta-analytic review of psychosocial interventions for substance use disorders found that treatments targeting polysubstance use were less effective and had the lowest percentage of posttreatment abstinence compared to other interventions for substance dependence 44.…”
Section: Discussionsupporting
confidence: 90%
“…These findings confirm previous research which showed a decrease in psychological distress during the early alcohol detoxification period 6,11,35,36. It is well known that addiction is associated with negative affectivity (eg, anxiety and depression) and that alcohol use in many cases can be considered as an avoidance coping strategy to escape from negative internal states and to reduce self-focused attention 10,24,37.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4 The wide variety of current treatment options includes drugs (eg, disulfiram), cognitive behavioral therapy (CBT), motivational reinforcement techniques, 12-step facilitation therapy, coping skills’ management, relapse prevention therapy, and family therapy. 5 The inpatient rehabilitation 28-day program 6 used in this study was inspired by the American Minnesota Model, 7 Croatian psychiatry studies, 8 and German and Austrian “psychosomatic clinics”. 9 It consisted of a series of highly structured interventions involving group psychotherapy, individual therapy (CBT), alcohol-related risk education sessions, and group activities and group meetings with family members to manage the patient’s medical and psychological problems.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown an overall reduction in anxious–depressive symptoms and a psychological improvement among alcoholics during the first weeks after detoxification. 6 , 10 , 11 However, some authors have found that the period after detoxification is at great risk of depressive symptoms and relapses and research is needed to examine factors associated with the maintenance of change and abstinence. 10 …”
Section: Introductionmentioning
confidence: 99%